2011
DOI: 10.1016/j.otsr.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-bearing unicompartmental knee arthroplasty. Patients’ selection and operative technique

Abstract: Unicompartmental knee arthroplasty (UKA) is designed for patients presenting arthritic wear limited to a single medial or lateral tibiofemoral compartment. The indication is based on strict criteria. Wear must stem from degenerative osteoarthritis or be secondary to aseptic necrosis of the medial condyle. Inflammatory rheumatism is a contraindication. Age and activity level should be compatible with an indication for arthroplasty. The body mass index should be less than 30 kg/m(2). The ligament system must be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 48 publications
0
50
1
1
Order By: Relevance
“…Kozinn and Scott [18] Bert [5] suggested that the ideal patient for UKA should be able to pinpoint their pain to the medial joint line (the 'one finger sign') rather than feeling pain generally within the knee (the 'knee grab sign'). Whilst no evidence-base exists to support this practice, it has been adopted by other authors as a prerequisite for UKA [10,14,27].…”
Section: Discussionmentioning
confidence: 99%
“…Kozinn and Scott [18] Bert [5] suggested that the ideal patient for UKA should be able to pinpoint their pain to the medial joint line (the 'one finger sign') rather than feeling pain generally within the knee (the 'knee grab sign'). Whilst no evidence-base exists to support this practice, it has been adopted by other authors as a prerequisite for UKA [10,14,27].…”
Section: Discussionmentioning
confidence: 99%
“…In case of excessive tibial cut, tibial component is placed to the more fragile cancellous zone, the contact point of the femoral pad shifts to the periphery of the tibial plateau that leads to tibial loosening (5,28,29). Minimal tibial resection leads to overcorrection, joint line elevation (30), and -according to our study -to degenerative changes in lateral tibiofemoral joint.…”
Section: Discussionmentioning
confidence: 60%
“…It should extend to the medial margin of the tibia or overhang by up to 2 mm (2, 3). There is no height difference between the line of tibial component joint surface and the lateral tibiofemoral joint space (LTF), the tibial component joint surface is parallel with the LTF joint space (4,5) and there is no change in tibial slope (TS) compared with the preoperative position in the sagittal plane (4,5). In frontal plane, the femoral component is perpendicular to the tibial component joint surface (4,5), the component is positioned centrally on the medial femoral condyle (6), in sagittal plane the anterior edge of femoral component is in the same level with the line of the remaining cartilage (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful outcomes with UKA require strict observation of indications [12]. One of the most important factors influencing long-term survival is the condition of cartilage in the opposite femorotibial compartment [48].…”
Section: Discussionmentioning
confidence: 99%